Introduction to cytogenetics 2 - SenGupta, Sioban (Henry Stewart Talks, 2010)
Genetic diversity, Meiosis I, Meiosis II, Synapsis, Recombination, Chiasmata, Sex chromosomes, Cell cycle checkpoints, Meiosis check points, Causes of aneuploidy, Non-disjunction during meiosis, Disruption of non-disjunction, Parental origin of aneuploidy, Gametogenesis, Oogenesis, Impact of maternal age, Production line hypothesis, Depleted oocyte hypothesis, Down syndrome, Chromosome abnormalities in humans, miscarriages and newborns